Effect of head and neck radiotherapy on the Eustachian tube functions - Ahmed Abdullah Hamd; Essam Abd El-Wanes Behiry; Adel Tharwat Atallah; Sherif Maher Elaini; Ahmed Hamdy Alshafai (The Egyptian Journal of Otolaryngology, 2020)
Abstract Background Nowadays, radiotherapy is widely used in management of many types of tumors including head and neck tumors; in this study, we concerned with its reverse effects on the Eustachian tube functions and if this effect is temporary or permanent. Results The whole (30) patients have tympanogram at both ears before starting radiotherapy; all patients (100%) were normal. In the immediate post radiotherapy tympanogram at the contralateral side, 6.7% of patients had effusion, and 20% had Eustachian tube dysfunction, while at the ipsilateral side, 20% of patients had effusion, and 33.3% had ET dysfunction. In the follow-up tympanogram 12 weeks post radiotherapy, we found that 6.7% of patients had effusion, and (10%) had Eustachian tube dysfunction at the contralateral side, while 6.7% of patients had effusion, and only 20% had Eustachian tube dysfunction at the ipsilateral side. Conclusion From this study, we concluded that patients with head and neck tumors treated by radiotherapy (apart from the nasopharynx) have a high incidence of affection of Eustachian tube function namely middle ear effusion and Eustachian tube dysfunction. The possibility for development of middle ear effusion and Eustachian tube dysfunction increases with increased tumor stage. Eustachian tube functions immediately post radiotherapy and after 12 weeks of the end of radiotherapy was affected by different effects according to the tumor site. The Eustachian tube functions significantly improved within 12 weeks after the last dose of radiotherapy, and we recommend audiological follow-up for patients with head and neck tumors treated with radiotherapy.